PERLINDUNGAN TERHADAP PEMEGANG SAHAM MINORITAS BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Pangestu, Lintang Caesar; Noer, Zakiah; Dara (Cattleya Darmaya Fortuna, 2026)
This study analyzes the legal reconstruction of minority shareholder protection under Law No. 40 of 2007 in Indonesia, focusing on special rights and fiduciary duties. Using normative legal research with statute and case approaches, the study identifies a disconnect between formal regulations and substantive justice, often leading to